Experimental and Numerical Investigation of Fiber Direction on The Vibration Properties of Ananas Comosus Leaf Reinforced Epoxy Composite Beams - Syaiful Syaiful; Randis Randis (Green Engineering Society, 2023)
Technological evolution and environmental awareness have driven the improvement of quality and renewable products, especially in natural fiber-reinforced composites. This study aims to analyze the stiffness and personal frequency of ACL fiber-reinforced composite beams due to the influence of the fiber direction. Next, compare experimental values with numerical. Composite beams are produced by varying the direction of the fibers 0°/0°/0°, -45°/0°/45° and -90°/0°/90° then supported by a simple support (clamp-roll). The exciter position is placed at 0-50 cm along the composite beam, then determine the value of stiffness and vibration behavior experimentally and numerically. This research indicates an increase in the stiffness and personal frequency of composite beams in the fiber direction 0°/0°/0°. The experimental values are also greater when compared to the values obtained numerically. These findings make it possible to use ACL fiber to manufacture composite beams with vibration-enabled characteristics for various applications in engineering materials subject to vibrational forces